Practices of intercultural competence teaching: an autobiographical study at aviation English classroom - Furyanto, Faoyan Agus; Rochmawati, Laila (Journal of Education and Learning (EduLearn), 2025)
The practice of intercultural teaching seems to be commonly applied but not in aviation English class. This might be difficult in conceptualizing intercultural competence instructional model (ICCIM) due to the mandatory adaptation to aviation English materials. This autobiographical study aimed to describe how the researcher conducted intercultural competence (ICC) teaching in aviation English class along with the depiction of students’ reflective constructs. This study was undertaken in Politeknik Penerbangan Surabaya as one of state aviation schools under agency of human resource development on transportation. The researcher found that the ICCIM could be implemented in aviation English class with some challenges. Another finding showed that the students were interested in learning ICC materials. This autobiographical study implies that there needs further research in examining ICCIM in aviation English class with wider cultural exposures and practices to give aviation students wider cultural perspectives before they work in the field of aviation.